Health Literacy of Planetary Diets: Key for Nutritional Health, Obesity Epidemic and Environmental Sustainability - Alice M. L. Li (Disease and Health Research: New Insights Vol. 2, 2024)
Empirical studies reviewed that health literacy on planetary health diets is now being recognized as the interlinks between environmental sustainability, nutritional health and the obesity epidemic. In 2022, 2.5 billion adults were overweight globally, including 890 million who were living with obesity, which is a known mediator in the relationship between diet and cardiovascular disease. Today cardiovascular disease is still the leading cause of diet-related deaths globally. And obesity-related non-communicable diseases also come at great cost to the global community and are arising in line with the current unsustainable dietary trend. Despite livestock products providing one-third of humanity’s protein intake, however, they are a contributing cause of obesity and the top two or three most significant contributors to the most serious ecological problems that intensify adverse impacts on our eco-environments with substantial greenhouse gas sources that drive climate change. This paper synthesized the signification of health literacy on planetary health diets, as an integral part of nutrition transition under this age of eco-environmental and climate-mediated health risks during the Anthropocene transition. It is utterly critical to the challenges of ecological public health towards the trend of planetary health diets in this 21st century. And that will require systemic approaches that take full account of social, economic, ecological and evolutionary factors. Thus, all health professionals should recognize the need to keep abreast with this evolving health literacy by necessitating a holistic notion of ecological public health education towards the 22nd century.